11-β-hydroxysterols as possible endogenous stimulators of mitochondrial biogenesis as inferred from epicatechin molecular mimicry. (January 2020) - Dugar, Sundeep; Villarreal, Francisco; Hollinger, Frank H.; Mahajan, Dinesh; Ramirez-Sanchez, Israel; Moreno-Ulloa, Aldo; Ceballos, Guillermo; Schreiner, George
Graphical abstract: Abstract: Currently, there is great interest in identifying endogenous (i.e. physiological) stimulators of mitochondrial biogenesis (MB), in particular, those that may mediate the effects of exercise. The molecular size of the cacao flavanols (epicatechin and catechin) highly resembles that of sterols and epicatechin has been reported to activate cells surface receptors leading to the stimulation of MB in endothelial and skeletal muscle cells translating into enhanced exercise capacity. We therefore hypothesize, that epicatechin may be acting as a structural mimic of an as yet unknown sterol capable of stimulating MB. We developed a new synthetic process for obtaining enantiomerically pure preparations of (-)-epicatechin and (+)-epicatechin. Applying spatial analytics and molecular modeling, we found that the two isoforms of epicatechin, (-) and (+), have a structural resemblance to 11-β-hydroxypregnenolone, a sterol with no previously described biological activity. As reported in this proof-of-concept study performed in primary cultures of endothelial and muscle cells, 11-β-hydroxypregnenolone is one of the most potent inducers of MB as significant activity can be detected at femtomolar levels. The relative potency of (-)/(+)-epicatechin isoforms and on inducing MB correlates with their degree of spatial homology towards the 11-β-hydroxypregnenolone. On the basis of these results, the detailed in vivo characterization of the potential for these sterols to act as endogenous modulators of MB is warranted.